Towards a policy of differentiated method of reservation in the light of Gujarat stir - Trivedi, Harshad R (1990)
Issues relevant to reservation policy are discussed in the light of the anti-reservation stir in gujarat in 1985, which later got transformed into serious communal conflict. The author finds that though preferential form of reservation has persisted with us since long as a cultural tradition, both in private and public sector, yet new factors like individualism, equality, rationality, etc. are causing conflict situations and pushing us to the present predicament. As is obvious, working out an all-embracing formula of reservation policy, keeping in view social and economic backwardness is a highly complicated exercise as has been proved by Levi-strauss. To get over this problem author has proposed a model
Keywords: Employment; Reservation; Policy; Reservation - Employment - India - Gujarat; Reservation - Employment